A Strong Call for Content: reflecting on Austria´s Needs in CLIL Vocational Schools - Wolfgang WÖGERER (Edukacja Ustawiczna Dorosłych)
Austria has quite an experience in vocational CLIL. It has been implemented on a compulsory level, and now it is a method of teaching in about one hundred Austrian schools and this number is rising. In the last few years about three hundred Austrian vocational teachers have successfully completed a CLIL course at Pädagogische Hochschule Wien. The project “CLIL-VET – Implementing the CLIL-VET model in vocational schools” with partners from Poland, Romania and Spain offered a possibility to take a step back and view CLIL in Austria through another perspective. Especially the differences in vocational teaching and language proficiencies of teachers and students in other countries gave us a chance to explore the needs of Austrian vocational CLIL. This paper is a strong call for content in vocational CLIL. The need for improvement roots in different factors, some of which are the language proficiencies of vocational CLIL teachers and students and the CLIL subject’s content. This paper describes two methods of pushing vocational content, both using translanguaging.